How to treat a neonate with duodenal atresia and intrapancreatic choledochocele causing persistent hyperbilirubinemia: A case report. (2016) - Zoetsch, Silvia; Singer, Georg; Sorantin, Erich; Flake, Alan W.; Till, Holger
Highlights: We report the first case of duodenal atresia and choledochocele requiring surgical treatment in the neonatal period. The patient received a classical duodeno-duodenostomy on day 2 of life. The choledochocele was treated with transduodenal marsupialization at the age of three months. A life-long observation seems mandatory to examine the potential risk of metaplasia in the cystic remnant. Abstract: Introduction: The congenital combination of duodenal atresia and choledochal cyst has only been reported in a few children. None of these patients had an intrapancreatic choledochocele causing persistent hyperbilirubinemia in the newborn period. Presentation of case: A female newborn presented with duodenal atresia and received a duodeno–duodenostomy on day two of life. The postoperative course was uneventful except for progressive hyperbilirubinemia and elevation of liver enzymes. No evidence for surgical obstruction, malformations of the hepatobiliary system, or infectious diseases were found. At three months of age and persistent hyperbilirubinemia an intrapancreatic choledochocele type III according to Todani was confirmed by ultrasound and MRI. Upon laparotomy no lesion was visible or palpable within the pancreas. Even after duodenotomy distally of the duodeno–duodenostomy only a normal papilla Vateri could be identified. Transduodenal ultrasound allowed for localization and saline distension to outline the borders of the choledochocele. A transduodenal marsupialization provided immediate biliary drainage and postoperatively bilirubin levels returned to normal limits. Discussion: We present a case of duodenal atresia and choledochocele requiring surgical treatment in the neonatal period. Transduodenal marsupialization prompted adequate biliary drainage without inflicting the potential complications of biliary and pancreatic diversion at this early age. A life-long endoscopic observation seems mandatory to examine the potential risk of metaplasia of the cystic remnant. Conclusion: Early transduodenal marsupialization of an intrapancreatic choledochocele in a case of duodenal atresia is safe and feasible to prevent secondary liver cirrhosis.